2007
DOI: 10.1142/s0192415x07005247
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of DeQi Sensation by Visual Analog Scales in Healthy Humans after Immunostimulating Acupuncture Treatment

Abstract: Acupuncture is the most popular component of traditional Chinese medicine in Western countries. However, the mechanisms of its effects remain unclear. The therapeutic effect of acupuncture appears when a sensation of DeQi is achieved. We previously reported that repeated, but not single acupuncture treatment affected leukocyte circulation and blood pressure in healthy young humans. The objective of this study was to quantify DeQi sensation by using visual analog scales (VASs) and, to test whether DeQi inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…However, several clinical trials have shown that real acupuncture needling, especially with rotation, can elicit higher intensity sensations than sham or superficial needling. 5,7,21,23,27 Our observed rate of complete recovery in the control group (77.1% of patients) is similar to that in the corticosteroid group (76.7%) in a recent Cochrane review, 28 which suggests that patients in our control group had similar experiences to patients who received sham acupuncture.…”
Section: Limitationssupporting
confidence: 81%
See 1 more Smart Citation
“…However, several clinical trials have shown that real acupuncture needling, especially with rotation, can elicit higher intensity sensations than sham or superficial needling. 5,7,21,23,27 Our observed rate of complete recovery in the control group (77.1% of patients) is similar to that in the corticosteroid group (76.7%) in a recent Cochrane review, 28 which suggests that patients in our control group had similar experiences to patients who received sham acupuncture.…”
Section: Limitationssupporting
confidence: 81%
“…Intensity was rated using a visual analogue scale ( Figure 1), which has commonly been used to measure the intensity of de qi. [21][22][23] The patient was asked to indicate his or her response to each sensation anywhere on the continuum. The score for the visual analogue scale was the sum of all 8 component scores.…”
Section: Assessment Of De Qimentioning
confidence: 99%
“…These studies report similar fi ndings to ours that needle sensations associated with insertion of needles into deep soft tissue, include throbbing, stabbing, heaviness soreness and aching with the intensities of these sensations increasing during rotation of the needle. 5 9 15-17 Kou et al 12 found that deep acupuncture generated higher intensities of acupuncture needle sensation ratings of numbness, pressure, heaviness, warmth, radiating paraethesia when compared to superfi cial needling in eight healthy participants. In our study, throbbing and to some extent stabbing, tingling, heaviness, soreness and aching were associated with bidirectional rotation of a needle inserted into deep tissues.…”
Section: Discussionmentioning
confidence: 99%
“…12 They also completed the SASS 5 which uses 100 mm VAS to record the intensity of the following acupuncture needle sensations; stabbing, throbbing, aching, tingling, heaviness, soreness, numbness, fullness and burning. Participants recorded needle sensations onto paper sheets that remained out of view from the principal investigator until the end of the experiment.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…9 The Massachusetts General Hospital Acupuncture Sensation Scale has been used to balance breadth and depth of sensations as well as the number of different sensations chosen by subjects. 10 Other similar studies include the Subjective Acupuncture Sensation Scale (SASS), 11 visual analogue scales (VAS) 12 and the Southampton Needle Sensation Questionnaire (SNSQ). 13 Mechanisms of de qi have been more and more frequently examined in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%